1992
DOI: 10.1111/j.1751-1097.1992.tb04253.x
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrin Photosensitization of Multi‐drug Resistant Cell Types

Abstract: The P388 murine leukemia and P388/ADR, a subline expressing the multi-drug resistance (MDR) phenotype, were examined with regard to the role of MDR as a determinant of responsiveness to photodynamic therapy in vitro. Mesoporphyrin was used as a model substrate. We found no differences in porphyrin accumulation nor transport alterations associated with exposure of P388/ADR cells to the verapamil analog DMDP. There was a significant correlation between photodamage to mitochondria vs loss of cell viability in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 9 publications
2
29
0
Order By: Relevance
“…We therefore suggest that the resistance of the MES-SA/Dx5 cells to PDT cannot be attributed to the overexpression of P-gp, which is in accordance with other studies showing that chlorins and porphyrin-based photosensitizers are not substrates for P-gp (Capella and Capella, 2003). Previously, it was shown that murine leukemia P388/ADR cells were not cross-resistant to mesoporphyrin-PDT (Kessel and Erickson, 1992). However, later it was demonstrated that MDR cells can be cross-resistant to PDT because of impaired cellular accumulation of photosensitizers due to P-gp efflux pump activity (Kessel et al, 1994).…”
Section: Discussionsupporting
confidence: 73%
“…We therefore suggest that the resistance of the MES-SA/Dx5 cells to PDT cannot be attributed to the overexpression of P-gp, which is in accordance with other studies showing that chlorins and porphyrin-based photosensitizers are not substrates for P-gp (Capella and Capella, 2003). Previously, it was shown that murine leukemia P388/ADR cells were not cross-resistant to mesoporphyrin-PDT (Kessel and Erickson, 1992). However, later it was demonstrated that MDR cells can be cross-resistant to PDT because of impaired cellular accumulation of photosensitizers due to P-gp efflux pump activity (Kessel et al, 1994).…”
Section: Discussionsupporting
confidence: 73%
“…Several authors evaluated the phototoxicity of a number of dyes in MDR cells, with very good results. For example, it was shown that MDR murine leukemia cells are not cross-resistant to photosensitization by mesoporphyrin [18]. The photodynamic efficacy of a monocationic porphyrin which is not recognized by the multidrug transporter in murine leukemia cells in culture and in fibrosarcomas in vivo was also studied [21].…”
Section: Pdt Of Mdr Tumor Cellsmentioning
confidence: 99%
“…Talaporfi n-mediated PDT may have effi cacy in treating hepatocellular carcinoma, whereas Foscan ® looked promising in the treatment of pancreatic cancer (Kessel and Erickson 1992 ). In the case of prostate cancer, Foscan ® , Tookad Tookad, and Lutex Tookad, looked minimally invasive alternatives to surgery or radiotherapy , reducing the risk of the post-surgical side effects of incontinence and impotence.…”
Section: Clinical Pdt For Cancermentioning
confidence: 98%
“…This should be of special importance in elderly or debilitated patients who poorly tolerate more intensive therapeutic regimens. Moreover, considering its unique singlet oxygen-dependent cytotoxic effects, PDT can be safely combined with other antitumor treatments without the risk of inducing cross-resistance (Kessel and Erickson 1992 ). However, there have been few studies on combinations of PDT with standard antitumor regimens published to date (Zuluaga and Lange 2008 ).…”
Section: Pdt Combined To Other Treatment Modalities In Cancermentioning
confidence: 99%